REVIEW: EVALUASI RASIONALITAS PENGGUNAAN OBAT ANTIHIPERTENSI DI BEBERAPA RUMAH SAKIT DI INDONESIA - Gusdilla, Windy; Hermanto, Faizal (Jurnal Buana Farma, 2025)
Approximately 1 billion people, or about a quarter of the world's adult population, are estimated to suffer from hypertension, and this number continues to grow. By 2025, the number of people with hypertension is predicted to reach 1.6 billion. Inaccuracy in the use of drugs can lead to increased morbidity and mortality, especially in patients with chronic diseases. Therefore, the selection of drugs must always follow the established treatment standards. This review article aims to evaluate the rationality of the use of antihypertensive drugs in several hospitals in Indonesia. The method used is a narrative literature review through a search of 11 articles with publication years 2019-2024. Literature searches were conducted on the Google Scholar, PubMed, and ScienceDirect databases. The keywords used in the search are "Antihypertension and "Rationality". The results of the literature review indicate that the use of antihypertensive drugs in the hospital has been rational based on accurate diagnosis, accurate indication, accurate drug selection, accurate dosage, accurate method of administering drugs, accurate interval of administration, accurate duration of administration, and accurate assessment of patient conditions in accordance with existing therapy guidelines. Evaluation of the rationality of the use of antihypertensive drugs shows that the practice of this treatment in several hospitals in Indonesia is in accordance with the established standards, the use of antihypertensive drugs in the hospital is quite effective and safe for patients.